Comprehensive evaluation of an emergency monovalent SAT1 foot-and-mouth-disease vaccine: Antigen quality, product consistency, and protective efficacy - Mohamed Samy Abousenna; Nermeen G. Shafik; Sara E.A. El Sawy; Amal Abd El Moneim Mohamed; Heba A. Khafagy; Ehab El-Sayed Ibrahim; Wael Elfeil; Mohamed Ahmed Saad; Samir A. Nassif (PLoS ONE, 2026)
Foot-and-mouth disease (FMD) remains endemic in Egypt, with periodic incursions of antigenically distinct virus lineages. In 2025, FMDV serotype SAT1/topotype I was detected in Egypt for the first time, creating an immunity gap in a livestock population previously vaccinated against serotypes O, A, and SAT2. This study aimed to evaluate the quality, immunogenicity, antigenic relationships, and protective efficacy of an emergency inactivated monovalent SAT1 vaccine and to assess potential cross-reactivity with SAT2 vaccine strains. An inactivated SAT1 monovalent vaccine was produced under emergency conditions and subjected to in-process and final product quality control testing, including sterility, safety, RT-qPCR verification, and 146S antigen quantification. Neutralizing antibody responses were measured by virus neutralization test (VNT) at 28 days post-vaccination. Antigenic relationships between SAT1 and SAT2 strains were assessed using r₁-value analysis. Protective efficacy was evaluated by homologous challenge in vaccinated calves. All vaccine batches met quality control criteria, with consistent viral titers and 146S antigen content. Vaccinated calves developed a mean homologous VNT titer of 2.175 log₁₀ TCID₅₀, exceeding the WOAH protective threshold (≥1.65 log₁₀ TCID₅₀). Following homologous challenge, 100% (8/8) of vaccinated calves were clinically protected. In contrast, heterologous VNT titers against SAT2 strains were low (0.26–0.30 log₁₀ TCID₅₀), and r₁-values ranged from 0.12 to 0.14, below the WOAH threshold for antigenic matching (0.3). The emergency SAT1 monovalent vaccine induced strong homologous immunity and complete protection against SAT1 challenge. Limited antigenic and serological cross-reactivity with SAT2 confirms the serotype-specific nature of FMD immunity and supports the need for dedicated SAT1 vaccination and ongoing antigenic surveillance.